Effectiveness of bionematicide from Purpureocillium lilacinum in controlling root-knot nematodes (Meloidogyne spp.) - Swibawa, I Gede; Fitriana, Yuyun; Fiandani, Ambar; Suharjo, Radix; Solikhin, Solikhin; Purnomo, Purnomo; Susilo, F.X. (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
This research aimed to study the efficacy of the fungus Purpureocillium lilacinum as a bionematicide to control root-knot nematodes (RKN). Two steps of experiments were carried out in this study. The first experiment involved the application of various levels of bionematicide doses to control RKN on tomato plants. The second experiment tested the application of bionematicide (both as a single application and in combination with bromelain compost) to control RKN on guava cv. Kristal. A carbofuran nematicide was applied following the company’s recommendation in this second experiment for comparison. The results of the first trial showed that the application of P. lilacinum bionematicide at doses ranging from 20–40 g per plant or 7–13 g per kg of soil was effective in reducing the J-2 RKN population in the soil and roots, as well as mitigating damage to plant roots. In the second experiment, it was shown that the application of P. lilacinum bionematicide, either alone or mixed with bromelain compost, was more effective than the application of carbofuran nematicide in reducing the J-2 RKN population in the soil and roots, as well as in minimizing root damage to guava seedlings. Additionally, the application of bionematicides mixed with compost proved more effective than their single application in reducing plant root damage. Furthermore, apart from being able to control nematode populations and plant damage, P. lilacinum bionematicide could stimulate plant growth.